2018
DOI: 10.1021/acsami.7b15245
|View full text |Cite
|
Sign up to set email alerts
|

Tellurophene-Based Random Copolymers for High Responsivity and Detectivity Photodetectors

Abstract: Organic photodetectors (OPDs) have attracted great attention because of their advantages including tunable response range, easy processability, and flexibility. Various conjugated polymers have been developed for high-performing OPDs. Herein, a series of tellurophene-based random copolymers containing two typical electron-withdrawing units naphthalene diimide (NDI) and perylene diimide (PDI) are designed and synthesized. Through varying the ratio of PDI/NDI moieties of the analogous polymers, the optophysical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 59 publications
1
19
0
Order By: Relevance
“…An external voltage is applied to read out the photon‐derived carriers, and gain can be realized by multiple carrier recirculation. Since more than one electron can flow in consequence of a single absorbed photon, the EQE of >100% is possible, which means that an incident photon triggers an electrical current flow provided by numerous electrons …”
Section: Fundamentals Of Photodetectorsmentioning
confidence: 99%
“…An external voltage is applied to read out the photon‐derived carriers, and gain can be realized by multiple carrier recirculation. Since more than one electron can flow in consequence of a single absorbed photon, the EQE of >100% is possible, which means that an incident photon triggers an electrical current flow provided by numerous electrons …”
Section: Fundamentals Of Photodetectorsmentioning
confidence: 99%
“…In addition, the shot noise from the dark current as a major factor for the D * value is reported by much literature. [ 9 ] So, these parameters are calculated according to the following equations, [ 12,20,26 ] R=JphLI×(1T) G=R×hυq D=R2q×Jdark Here, J ph , J dark , hυ , and LI are the photocurrent density, dark current density, photon energy, and incident light intensity respectively; T is the transmission of light through the film (Table S1, Supporting Information) and q is the absolute value of electron charge.…”
Section: Methodsmentioning
confidence: 99%
“…[ 16,17 ] At present, there are many device physical approaches to improve the performance of BHJ photodetectors by changing the carrier injection mode, such as introducing a transport layer or a barrier layer and adjusting the energy level difference of asymmetric electrodes. [ 2,18–20 ] Besides, the intrinsic characteristics of materials including aggregation behavior or phase separation of polymers can also ultimately have a significant impact on the performance of polymer photodetectors. [ 21,22 ] However, the report received little advance on how to achieve phase control behavior in aggregated thin film devices and the way in which the carriers transfer.…”
Section: Introductionmentioning
confidence: 99%
“…[47] Through varying the molar ratio of PDI/NDI units, the physicochemical properties of the conjugated polymers were systematically investigated. [47] Through varying the molar ratio of PDI/NDI units, the physicochemical properties of the conjugated polymers were systematically investigated.…”
Section: Applications Of Tellurophene-based Polymersmentioning
confidence: 99%
“…Huang's group further developed another series of tellurophene-based copolymers P18 containing both NDI and PDI units in 2018. [47] Through varying the molar ratio of PDI/NDI units, the physicochemical properties of the conjugated polymers were systematically investigated. It was found that the favorite ratio of PDI/NDI units in P18 was 70/30 for organic photodetectors (OPDs), and P18 based devices demonstrated a high responsivity of 19.1 A/W at 600 nm and more than 10 12 Jones detectivity from 350 to 600 nm, which was among the best performances of OPDs.…”
Section: Applications Of Tellurophene-based Polymersmentioning
confidence: 99%